Modeling of aircrafts collision using importance sampling technique - Kharchenko, V. P.; Kukush, A. G.; Znakovskaya, E. A. (Proceedings of National Aviation University (archive), 2003)
We introduce the model of movement of two conflicting aircrafts and state the problem, we apply the importance sampling technique and elaborate an algorithm of collision modeling based on normal distributions, a small simulation study